Understanding the choices of terms of address: a sociolinguistic study of Malay cultural practices - Mansor, Nor Shahila; Abd Rahim, Normaliza; Mamat, Roslina; Abdul Halim, Hazlina (Islamic State University Sulthan Thaha Saifuddin Jambi, 2018)
This paper investigates the choices of second person terms of address in the Malay culture. It examines the different patterns of address terms used in a range of communicative situations by interlocutors coming from diverse social backgrounds. The data for this study was obtained from two Malay dramas Ijab & Qabul (The solemnization of marriage) and Tiga Hari Menanti Mati (Three Days Until Death). These dramas were selected because they reflect in the usage of terms of address in an authentic social context of the Malay culture and represent various interpersonal relationships in a range of situations. This is a descriptive study with a qualitative approach. Forty-eight different second person terms of address were recorded and analysed in specific contexts based on the framework for classifying address terms established by Kroger, Wood and Kim (1984). The findings suggest that sociolinguistic elements such as interlocutors, contexts, determinants of interpersonal relationship, and intentions were determining factors influencing the choice of second person terms of address in the Malay culture. These findings have implications on the understanding of current trends in choosing the terms of address among Malay speakers.